Radical Arab nationalism and political Islam - Addi, Lahouari 1949- (Georgetown University Press and The Center for Contemporary Arab Studies, Georgetown University Press, 2017)
Radical Arab nationalism emerged in the modern era as a response to European political and cultural domination, culminating in a series of military coups in the mid-20th century in Egypt, Algeria, Syria, Iraq, Yemen, and Libya. This movement heralded the dawn of modern, independent nations that would close the economic, social, scientific, and military gaps with the West while building a unity of Arab nations. But this dream failed. In fact, radical Arab nationalism became a barrier to civil peace and national cohesion, most tragically demonstrated in the case of Syria, for two reasons: 1) national armies militarized nationalism and its political objectives; 2) these nations did not keep pace with the intellectual and political and cultural and social progress of European nations that offered, for example, freedom of speech and thought. It was the failure of radical Arab nationalism, Addi contends, that made the more recent political Islam so popular. But if radical nationalism militarized politics, the Islamists politicized religion. Today, the prevailing medieval interpretation of Islam, defended by the Islamists, prevents these nations from making progress and achieving the kind of social justice that radical Arab nationalism once promised. Will political Islam fail, too? Can nations ruled by political Islam accommodate modernity? Their success or failure, Addi writes, depends upon this question